Strategi guru Pendidikan Agama Islam dalam meningkatkan kesadaran beribadah salat Duha pada siswa Sekolah Menengah Atas: Strategies of Islamic Education teachers in enhancing students’ awareness to perform Duha prayer at senior high school - Al Anshori, Muhammad Hafizh Rasyid; Palah, Palah; Nurmiati, Ai Siti; Komarudin, Komarudin (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2025)
This study aims to describe the strategies used by Islamic Education teachers to increase awareness of the duha prayer among high school students. The background of this study is the low awareness of some students in performing the duha prayer regularly. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation at SMA Plus Kembangkuning Ciambar, Sukabumi. The results show that teachers' strategies are carried out through worship habits, collaborative religious activities, and continuous evaluation. Teachers collaborate with the school in forming a spiritual culture through congregational duha prayer and student religious lectures. Evaluations were conducted periodically by monitoring student attendance, involvement, and attitude changes. These strategies proved effective in increasing worship awareness and shaping students' religious character. The conclusion of this study shows that Islamic Religious Education teacher strategies designed collaboratively and contextually can be a model for strengthening character education based on Islamic spiritual values.